English Teachers’ Perspective on Keeping a Teaching Journal as Their Professional Development - Eka Yuni Kurniati; Devika Adelita; Utami Dewi (Scope : Journal of English Language Teaching, 2023)
Keeping a teaching journal is one way that can be done to assist in the improvement of professional development. One approach that is becoming increasingly popular nowadays. Using a qualitative case study methodology, this research aims to explore the English teachers' perspectives on journal writing as a way of professional development. The study enlisted the participation of 21 English teachers to complete a demographic survey. In accordance with the aims of the study, participants were recruited using a technique of purposive sampling. In this case, the researcher selected the participant based on their experience in writing a teaching journal. The researcher utilized a questionnaire and an interview as instruments for data collection. The purpose of the questionnaire is to collect demographic information as well as respondents' perceptions about the benefit of keeping a teaching journal for professional development. The interview was then conducted to obtain further information regarding the participants' responses to the questionnaire. Five English teachers voluntarily participated in the interview process and in analyzing data, thematic content analysis was used in this study. The outcomes of the study revealed that English teachers got a range of benefits from strengthening their professional development, including encouraging a positive attitude toward teaching, enhancing English teachers' critical thinking, and improving teaching quality. This study suggested that keeping a teaching journal has a profound influence on English teacher development.